International Mobile Roaming: Progress and Challenges in African Markets - Sutherland, Ewan (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2011)
The persistence of high prices for international mobile roaming services, in contrast to falling national mobile prices, has been a recognised item on the global regulatory agenda for half a decade. In Africa, there have been studies and discussions about regulatory options in regional economic groups and in the various networks of national regulators. As yet, there has been no transnational regulatory action. Yet the initiative of one large operator saw the introduction of transnational tariff schemes (ie without a surcharge for roaming), forcing competitors to collaborate in order to respond, if they wished to attract and to retain customers. This has both saved money for consumers and greatly reduced the need for regulatory interventions that might have proved counterproductive. In some countries this type of offer remains impossible, because international gateways are a monopoly, having yet to be opened to competition.
Keywords: international mobile roaming, high IMR charges, African telecommunications sector, regulatory agenda